Formation mechanism of short-pitch rail corrugation on metro tangent tracks with resilient fasteners. Issue 6 (3rd June 2023) - Li, Wei; Zhou, Zhijun; Zhao, Xin; Wen, Zefeng; Jin, Xuesong
Abstract : A type of short-pitch rail corrugation on tracks with resilient fasteners called 'Vanguard' fasteners is widely found on different metro lines in China. Field measurements and numerical calculations are used to investigate the cause of the corrugation formation. The corrugation with wavelengths of 30–60 mm occurs on both the curved and straight tracks through field measurements. Corrugation passing frequencies are in the range of 340–700 Hz. The frequencies of pinned-pinned resonance, the P2 resonance and the wheelset torsional resonance are far away from the corrugation passing frequencies. The investigated results show the vertical dynamic characteristic of the track is the main factor for occurrence of the short-pitch rail corrugation. The short-pitch rail corrugation arises by a wavelength-fixing mechanism of rail vertical bouncing on the resilient fasteners. The corrugation wavelength mainly is related to the vertical stiffness of the rail fasteners. Rail corrugation with wavelengths of 25–63 mm easily occurs on tracks with resilient fasteners with the vertical stiffness of less than 20 MN/m.